2005
DOI: 10.1007/s00424-005-1419-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPC5 channels by Ca2+-binding protein 1 in Xenopus oocytes

Abstract: The transient receptor potential canonical type 5 (TRPC5) channel is a member of the channels that has been implicated in neurite extension and growth cone morphology of hippocampal neurons. Although homomeric TRPC5 channels are activated following stimulation of G(q/11)-coupled receptors, the exact mechanism for this activation remains unresolved. Using two-electrode voltage clamp recordings, we show that the activity of TRPC5 channels expressed in Xenopus oocytes is dependent on the presence of Ca2+ at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
(89 reference statements)
0
45
0
Order By: Relevance
“…Incidentally, the CIRB site is also critical for the Gα i/o effect on TRPC4 (3). Moreover, Ca 2+ exhibits both positive and negative effects on some TRPC channels (20,(24)(25)(26)(27)(28).…”
Section: Trpc4 Activation Requires Coincident G I/o Stimulation and Plcmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally, the CIRB site is also critical for the Gα i/o effect on TRPC4 (3). Moreover, Ca 2+ exhibits both positive and negative effects on some TRPC channels (20,(24)(25)(26)(27)(28).…”
Section: Trpc4 Activation Requires Coincident G I/o Stimulation and Plcmentioning
confidence: 99%
“…Therefore, in addition to supporting TRPC4 function, PIP 2 also exerts a tonic inhibition on the channel. (21,(24)(25)(26)(27)(28)32). To determine if IP 3 Rs are involved in TRPC4 activation, we applied the IP 3 R inhibitor heparin (3 mg/mL) by intracellular dialysis and found that most cells failed to respond to DAMGO and subsequent application of CCh (Fig.…”
Section: Trpc4 Activation Requires Coincident G I/o Stimulation and Plcmentioning
confidence: 99%
“…CaBPs bind to and yet differentially modulate a number of CaM targets, including voltage-gated Ca 2ϩ channels (Lee et al, 2002;Zhou et al, 2004;Yang et al, 2006), transient receptor potential TRP channels (Kinoshita-Kawada et al, 2005), and inositol 1,4,5-trisphosphate (IP 3 ) receptors (Yang et al, 2002;Haynes et al, 2004;Kasri et al, 2004). Through interactions with these and potentially other effectors, CaBPs may enhance the Ca 2ϩ signaling potential in neurons and other excitable cells.…”
Section: Introductionmentioning
confidence: 99%
“…CaBPs are calmodulin-like proteins that use three functional out of four helix-loop-helix domains (EF-hand) for Ca 2+ binding (27). They are thought to function primarily as signaling proteins (28) and differentially modulate calmodulin effectors (29,30). In addition, CaBPs might also contribute in buffering free cytosoloic Ca 2+ ions, as do other small EF-hand calcium-binding proteins, such as calretinin, calbindin-D-28k, and parvalbumin-α (31-33).…”
mentioning
confidence: 99%